The Astaxanthin Aggregation Pattern Greatly Influences Its Antioxidant Activity: A Comparative Study in Caco-2 Cells - Mingqin Dai; Chunjun Li; Zhao Yang; Zhe Sui; Jing Li; Ping Dong; Xingguo Liang (MDPI AG, 2020)
Astaxanthin is an excellent antioxidant that can form unstable aggregates in biological or artificial systems. The changes of astaxanthin properties caused by molecular aggregation have gained much attention recently. Here, water-dispersible astaxanthin H- and J-aggregates were fabricated and stabilized by a natural DNA/chitosan nanocomplex (respectively noted as H-ADC and J-ADC), as evidenced by ultraviolet and visible spectrophotometry, Fourier transform infrared spectroscopy, and Raman spectroscopy. Compared with J-ADC, H-ADC with equivalent astaxanthin loading capacity and encapsulation efficiency showed smaller particle size and similar zeta potential. To explore the antioxidant differences between astaxanthin H- and J-aggregates, H-ADC and J-ADC were subjected to H2O2-pretreated Caco-2 cells. Compared with astaxanthin monomers and J-aggregates, H-aggregates showed a better cytoprotective effect by promoting scavenging of intracellular reactive oxygen species. Furthermore, in vitro 1,1-diphenyl-2-picrylhydrazyl and hydroxyl free radical scavenging studies confirmed a higher efficiency of H-aggregates than J-aggregates or astaxanthin monomers. These findings give inspiration to the precise design of carotenoid aggregates for efficient utilization.